Feasibility Study of a Piezo Actuator as a Potential Standard in Calibration for Roundness Instruments - Anna Trych-Wildner; Krzysztof Wildner; Piotr Sosinowski (Sensors, 2022)
The paper presents experimental data that show the possible application of a piezo actuator in the role of calibration standard that can serve as an alternative route to currently available methods like gauge blocks or flick standards. First, the experimental setups for interferometric and roundness instruments measurements were described. Next, the experiments using an interferometer for calibration of the piezo actuator were shown. Finally, the application of a piezo actuator to calibrate the roundness instrument, to state the correction factor for the roundness probe, and to relate it to the unit of metre, assuring the traceability of future measurements was performed. Detailed procedures of simulating grooves and then processing the data were described and the calibration curve was obtained using regression analysis. The estimation of uncertainty provided by different factors during the measurements was given to fulfil as closely as possible real calibration procedures taken up in the measurement laboratories. Finally, the limitations of the presented procedures were presented and discussed.